Unveiling Thrombocytopenia Trends In Pediatric Epilepsy: The Valproate Connection - Kiran Nayab; Qurrat ul Ain; Ayesha Tariq; Israr Liaqat; Samra Javed; Nadia Mumtaz (Journal of Rawalpindi Medical College)
Objective: To determine the frequency and association of thrombocytopenia in patients on valproate therapy in the Pediatrics department of Pakistan Atomic Energy Hospital, Islamabad.